Effects of Sulfurization Temperature on Properties of CZTS Films by Vacuum Evaporation and Sulfurization Method - Jie Zhang; Bo Long; Shuying Cheng; Weibo Zhang (International Journal of Photoenergy)
Copper zinc tin sulfur (CZTS) thin films have been extensively studied in recent years for their advantages of low cost, high absorption coefficient (≥104 cm−1), appropriate band gap (~1.5 eV), and nontoxicity. CZTS thin films are promising materials of solar cells like copper indium gallium selenide (CIGS). In this work, CZTS thin films were prepared on glass substrates by vacuum evaporation and sulfurization method. Sn/Cu/ZnS (CZT) precursors were deposited by thermal evaporation and then sulfurized in N2 + H2S atmosphere at temperatures of 360–560°C to produce polycrystalline CZTS thin films. It is found that there are some impurity phases in the thin films with the sulfurization temperature less than 500°C, and the crystallite size of CZTS is quite small. With the further increase of the sulfurization temperature, the obtained thin films exhibit preferred (112) orientation with larger crystallite size and higher density. When the sulfurization temperature is 500°C, the band gap energy, resistivity, carrier concentration, and mobility of the CZTS thin films are 1.49 eV, 9.37 Ω · cm, 1.714×1017 cm−3, and 3.89 cm2/(V · s), respectively. Therefore, the prepared CZTS thin films are suitable for absorbers of solar cells.